FeCo alloy / graphene foam composite material and preparation and application thereof
By combining FeCo alloy particles with graphene foam, the FeCo alloy/graphene foam composite material is prepared by hydrothermal method, which solves the application restriction caused by poor agglomeration and dispersion of graphene materials, and achieves better electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202311079410.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing graphene absorbing materials are prone to agglomeration and poor dispersion due to their huge specific surface area, which leads to the problems of uneven distribution and high filling ratio in their applications, which limits their wide application in the field of electromagnetic wave absorption.
FeCo alloy particles are used to composite the graphene foam. The FeCo alloy particles are loaded on the surface of the graphene foam and embedded between its sheet layer and pores. The FeCo alloy/graphene foam composite material is prepared by hydrothermal method.
It improves the impedance matching performance of graphene foam, enhances its attenuation and absorption capacity of electromagnetic waves, and solves the problem of limited application of graphene materials in the field of electromagnetic wave absorption.
Smart Images

Figure CN119521636A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a FeCo alloy / graphene foam composite material and preparation and application thereof, belonging to the technical field of materials, in particular to the technical field of electromagnetic wave absorption materials. Background Art
[0002] With the advent of the 5G era, the research and development of electronic information technology has ushered in another climax. At the same time, the application of electromagnetic waves in the fields of medical, industry and commerce, aerospace, electronic communications, etc. has become more and more extensive. However, with the widespread application of technologies such as wireless communication, radar, and satellite communication, the radiation of electromagnetic waves has continued to increase, making electromagnetic wave pollution a global environmental problem, posing an increasing threat to human health and living environment. The radiation of electromagnetic waves can cause DNA damage to human cells, immune system disorders, nervous system disorders, and other problems. Long-term exposure may also cause diseases such as cancer. In addition, the radiation of electromagnetic waves can also interfere with and damage the normal operation of electronic equipment. In the military field, with the continuous development of reconnaissance and detection equipment represented by integrated detection and strike drones, the living environment of main combat equipment on the battlefield has continued to deteriorate. Absorbing materials are materials that can absorb electromagnetic waves and convert them into other energy, which can effectively reduce the radiation of electromagnetic waves. Therefore, the design and development of high-performance microwave absorbing materials to reduce electromagnetic pollution and consolidate national defense security has become a current research hotspot.
[0003] Among the many absorbers that have been reported, graphene materials have attracted widespread attention due to their advantages such as low density, high specific surface area, good conductivity and dielectric properties. At the same time, graphene oxide and reduced graphene oxide derived from graphene have better impedance matching performance and electromagnetic attenuation capabilities due to their more defects and oxygen-containing functional groups, and have become a research hotspot in recent years. The emergence of graphene materials is expected to overcome the shortcomings of traditional absorbers such as ferrites and ceramics, such as high density and narrow absorption band, and better meet the requirements of "thin, light, wide and strong" for absorbers. However, graphene is prone to agglomeration due to its huge specific surface area. When mixed with paraffin as a filler, it has poor dispersion and uneven distribution. In order to reflect its good dielectric loss, a large filling ratio is often required, which seriously limits the application of graphene absorbers.
[0004] To solve this problem, researchers have developed three-dimensional graphene absorbing materials. Although three-dimensional graphene absorbing materials have overcome the agglomeration problem, they also show better dielectric properties and lower density. At the same time, the reflection, scattering and interference of electromagnetic waves by the internal pore structure of three-dimensional graphene are also its unique advantages as an absorbing material. However, three-dimensional graphene is an electrical loss material and does not have magnetic loss capabilities, so its impedance matching performance is poor. It needs to be compounded with magnetic loss materials to improve impedance matching performance and further improve the attenuation and absorption of electromagnetic waves. Typical magnetic loss absorbing materials mainly include ferrites and magnetic metal particles.
[0005] Therefore, providing a new FeCo alloy / graphene foam composite material and its preparation and application has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a FeCo alloy / graphene foam composite material.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned FeCo alloy / graphene foam composite material.
[0008] Another object of the present invention is to provide application of the above-mentioned FeCo alloy / graphene foam composite material as a wave absorbing material.
[0009] In order to achieve the above objectives, on the one hand, the present invention provides a FeCo alloy / graphene foam composite material, wherein the FeCo alloy / graphene foam composite material comprises FeCo alloy particles and graphene foam, wherein the FeCo alloy particles are loaded on the surface of the graphene foam and embedded between the flakes and pores of the graphene foam.
[0010] As a specific embodiment of the FeCo alloy / graphene foam composite material described above in the present invention, the content of graphene foam is 0.5%-4.5%, preferably 1%-4%, and more preferably 2%-4%, based on the total weight of the FeCo alloy particles as 100%.
[0011] As a specific embodiment of the FeCo alloy / graphene foam composite material described above, the graphene foam has a three-dimensional porous network structure and a density of 0.012-0.030 g / cm 3 , the maximum value of the real part of the dielectric constant is 6-12.
[0012] On the other hand, the present invention also provides a method for preparing the above-mentioned FeCo alloy / graphene foam composite material, wherein the preparation method comprises:
[0013] Step 1: adding a divalent iron source, a divalent cobalt source and graphene foam powder into deionized water and mixing them evenly to obtain a metal precursor solution;
[0014] Step 2: completely dissolving the alkali source in deionized water to obtain an alkali source aqueous solution;
[0015] Step 3: dropping the alkaline source aqueous solution into the metal precursor solution and mixing evenly, then adding the reducing agent and mixing evenly to obtain a mixed solution;
[0016] Step 4: subjecting the mixed solution to a hydrothermal reaction. After the hydrothermal reaction is completed, collecting the black precipitate and drying it to obtain the FeCo alloy / graphene foam composite material.
[0017] As a specific embodiment of the preparation method described above, in step 1, the divalent iron source includes one or a combination of ferrous chloride, ferrous sulfate, ferrous nitrate and ferrous acetate, and the divalent cobalt source includes one or a combination of cobalt chloride, cobalt sulfate, cobalt nitrate and cobalt acetate. In addition, in step 1, the molar ratio of divalent iron ions to divalent cobalt ions is 1:1.
[0018] As a specific embodiment of the preparation method described above of the present invention, in step 1, the graphene foam is prepared by a preparation method comprising the following specific steps:
[0019] Step (1): mixing graphene oxide slurry with a reducing agent, and adding a pore-forming agent to the resulting mixed solution under stirring conditions;
[0020] Step (2): subjecting the mixed solution obtained in step (1) to a hydrothermal reaction;
[0021] Step (3): vacuum drying the graphene gel obtained in the reaction in step (2) to obtain the graphene foam.
[0022] As a specific embodiment of the preparation method described above, step (3) comprises: after the product obtained by the reaction in step (2) is naturally cooled, vacuum drying the obtained graphene gel.
[0023] As a specific embodiment of the preparation method described above in the present invention, in step (1), the volume ratio of the graphene oxide slurry to the reducing agent is 1:1-1:2, and the volume ratio of the mixed solution formed by the graphene oxide slurry and the reducing agent to the mass ratio of the pore-forming agent is 3:1-6:1.
[0024] As a specific embodiment of the preparation method described above in the present invention, in step (1), the concentration of the graphene oxide slurry is 1-3 mg / mL.
[0025] As a specific embodiment of the preparation method described above of the present invention, in step (1), the pore-forming agent includes a pore-forming agent that can sublime under the temperature conditions of hydrothermal reaction and vacuum drying; preferably, the pore-forming agent includes naphthalene, iodine or camphor balls.
[0026] As a specific embodiment of the preparation method described above of the present invention, in step (1), the reducing agent includes ethylene glycol, ethanol, sodium ascorbate aqueous solution or sodium hypophosphite aqueous solution, etc.
[0027] As a specific embodiment of the preparation method described above of the present invention, in step (2), the temperature of the hydrothermal reaction is 160-240° C. and the time is 8-16 hours.
[0028] As a specific embodiment of the preparation method described above of the present invention, wherein, in step (3), the vacuum drying comprises: first vacuum drying at 60-90°C for 40-60h, and then vacuum drying at 110-150°C for 32-48h.
[0029] As a specific embodiment of the preparation method described above, in step 2, the alkali source includes one or a combination of NaOH, urea and ammonia water, etc. The alkali source is used as a reaction balancer for the reduction reaction of iron ions and cobalt ions and provides an alkaline environment.
[0030] As a specific embodiment of the above preparation method of the present invention, the molar ratio of the alkali source to the divalent iron ion or the divalent cobalt ion is 10:1-20:1, preferably 15:1.
[0031] As a specific embodiment of the preparation method described above of the present invention, in step three, the reducing agent includes one or a combination of hydrazine hydrate, potassium borohydride and sodium borohydride.
[0032] As a specific embodiment of the above preparation method of the present invention, the molar ratio of the reducing agent to the divalent iron ion or the divalent cobalt ion is 60:1-100:1, more preferably 80:1.
[0033] As a specific embodiment of the preparation method described above of the present invention, in step 4, the temperature of the hydrothermal reaction is 150-170° C., and the time is 8-12 h.
[0034] As a specific embodiment of the preparation method described above of the present invention, in step 4, the drying is vacuum drying at a temperature of 60-80° C. for a time of 10-16 h.
[0035] In yet another aspect, the present invention further provides use of the above-mentioned FeCo alloy / graphene foam composite material as a wave absorbing material.
[0036] The FeCo alloy / graphene foam composite material provided by the present invention comprises FeCo alloy particles and graphene foam, wherein the FeCo alloy, as a typical soft magnetic material, has a higher saturation magnetization and a lower coercive force, which makes it easy to have a stronger magnetic loss capacity. At the same time, the preparation method of the FeCo alloy is simple and low-cost, and has the conditions for large-scale production. Graphene foam is a material with lower density and higher electrical conductivity, with excellent mechanical strength and stability, while the FeCo alloy has higher magnetic permeability and magnetic loss, and the two are compounded to effectively improve the impedance matching performance of the graphene foam. At the same time, their compounding can also produce a synergistic effect of electrical loss and magnetic loss, which is beneficial to improving the wave absorbing performance of the composite material, thereby being more conducive to solving the problem of electromagnetic wave pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is a physical picture of the graphene foam provided in Example 1 of the present invention.
[0039] Figure 2 This is a scanning electron microscope image of the graphene foam provided in Example 1 of the present invention.
[0040] Figure 3a-3e They are the SEM images of samples 1#-5# in Test Example 3 respectively.
[0041] Figure 3f This is the TEM image of sample 1# in test example 3.
[0042] Figure 3g This is the HRTEM image of sample 1# in test example 3.
[0043] Figure 4 This is the XRD spectrum of samples 1#-5# in Test Example 4.
[0044] Figure 5a This is the full XPS scan spectrum of sample 1# in Test Example 5.
[0045] Figure 5b This is the XPS scan C1s spectrum of sample #1 in Test Example 5.
[0046] Figure 5c This is the XPS scanning Fe2p spectrum of sample #1 in test example 5.
[0047] Figure 5d This is the XPS scanning Co2p spectrum of sample #1 in test example 5.
[0048] Figure 6a-6c They are respectively the three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of the 1# sample in Test Example 6.
[0049] Figure 6d-6f They are respectively the three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of the 2# sample in Test Example 6.
[0050] Figure 6g-Figure 6i They are respectively the three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of the 3# sample in Test Example 6.
[0051] Figure 6j-Figure 6l They are respectively the three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of the 4# sample in Test Example 6.
[0052] Figure 6m-Figure 6o They are respectively the three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of the 5# sample in Test Example 6. DETAILED DESCRIPTION
[0053] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0054] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0055] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0056] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0057] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0058] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0059] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0060] Example 1
[0061] This embodiment provides a series of FeCo alloy / graphene foam composite materials, which are prepared by a preparation method comprising the following specific steps:
[0062] Preparation of graphene foam:
[0063] Step (1): 170 mL of graphene oxide slurry (3 mg / ml) produced by Qitaihe Baotailong Graphene New Materials Co., Ltd. and model GO-S001 and 170 mL of ethylene glycol were measured and mixed to obtain a mixed solution;
[0064] Weigh 80 g of naphthalene, and slowly add 80 g of naphthalene to the mixed solution under mechanical stirring to obtain a suspension;
[0065] Step (2): transferring the suspension into a 500 mL polytetrafluoroethylene-lined reactor, performing a hydrothermal reaction at 200° C. for 12 h, and obtaining a graphene gel after the reaction is completed and cooled to room temperature;
[0066] Step (3): Take out the graphene gel and put it into a vacuum drying oven, vacuum dry it at 60°C for 48 hours, adjust the drying temperature to 120°C and vacuum dry it for another 36 hours to obtain graphene foam. Figure 1 As shown, its density is 0.0135g / cm 3 .
[0067] Preparation of FeCo alloy / graphene foam composites:
[0068] Step 1: Grind the graphene foam obtained above into powder in a mortar, and take 0.036g, 0.055g, 0.073g and 0.091g (accounting for 1%, 2%, 3% and 4% of the mass of FeCo alloy particles, respectively) for use; Put 3.184g FeCl2·4H2O (16mmol), 3.792g CoCl2·6H2O (16mmol) and a certain mass of graphene foam powder into 250mL deionized water, and ultrasonically treat for 10min to obtain a metal precursor solution;
[0069] Step 2: Take 9.6 g of NaOH and put it into 100 mL of deionized water, and ultrasonicate it for 10 min to completely dissolve the NaOH to obtain a NaOH aqueous solution;
[0070] Step 3: Drop the NaOH aqueous solution into the metal precursor solution, mix it evenly by ultrasonication for 10 min, and then add 80 mL of hydrazine hydrate (80 wt%, ρ is 1.0012 g / cm 3 ), and then subjected to ultrasonic treatment for 10 min to obtain a mixed solution;
[0071] Step 4: The mixed solution was transferred to a 500 mL polytetrafluoroethylene lined reactor, and a hydrothermal reaction was carried out at a temperature of 160°C for 10 hours. After the hydrothermal reaction, a black precipitate was collected by a magnet and vacuum dried at a temperature of 70°C for 12 hours to obtain a series of FeCo alloy / graphene foam composite materials. According to the amount of graphene foam powder added from small to large, a series of FeCo alloy / graphene foam composite materials were marked as 1#, 2#, 3# and 4#.
[0072] Comparative Example 1
[0073] This comparative example provides a FeCo alloy / graphene foam composite material, which differs from Example 1 only in that:
[0074] The amount of graphene foam powder used is 0.11 g (accounting for 5% of the mass of the FeCo alloy particles).
[0075] The FeCo alloy / graphene foam composite material prepared in this comparative example is marked as 5#.
[0076] Test Example 1
[0077] In this test example, the graphene foam prepared in Example 1 after being treated with liquid nitrogen was analyzed by scanning electron microscope. The results are as follows: Figure 2 As shown. Figure 2 It can be seen from the microscopic morphology of the graphene foam shown that the reduced graphene oxide layered flakes after the reduction of graphene oxide build up each other to form a three-dimensional porous structure, and the naphthalene content added in Example 1 is relatively moderate, which can be evenly and effectively filled into the entire graphene gel, so that the pore size distribution of the obtained graphene foam is relatively uniform, and the graphene layered structure is almost not observed in the graphene foam.
[0078] Test Example 2
[0079] This test example tests the wave absorption performance of the graphene foam obtained in Example 1, which includes: grinding the graphene foam and mixing it with paraffin (which plays a role in dispersion and solidification), and then testing the wave absorption performance of the obtained mixture (the specific test method can refer to the 1.2.4 electromagnetic parameter characterization section in "The Effect of Co Doping on the Microstructure and Wave Absorption Performance of RGO / Fe3O4 Composite Materials"), wherein the total weight of paraffin and graphene foam is 100%, and the addition amount of graphene foam is 2%. When the addition amount of graphene foam is 2%, the real part of the dielectric constant of the graphene foam is 9.932, and when the thickness of the graphene foam is 3.38mm, the minimum reflection loss can be obtained at a frequency of 8.48GHz, and the minimum reflection loss value is -55.89dB; when the thickness is 2.31mm, the effective bandwidth (reflection loss <-10dB) reaches 6.88GHz (11.12GHz-18GHz).
[0080] Test Example 3
[0081] In order to study the loading of FeCo alloy particles on the graphene foam surface in samples 1#-5#, SEM analysis was performed on them respectively in this test case. The obtained SEM images are as follows: Figure 3a-3e As shown. Figure 3a-3e It can be seen that the microscopic morphology of composite materials with different graphene foam contents shows great differences. Specifically, with the increase of graphene foam content in the composite material, the loading amount of FeCo alloy particles shows a relatively obvious downward trend, and the large FeCo alloy particles loaded on the surface of graphene foam are significantly reduced. This is because as the graphene foam content increases, the area that can be loaded by FeCo alloy particles also increases, so the loading density is significantly reduced. Figure 3a-3e It can also be found that the shape of the large FeCo alloy particles loaded on the surface of graphene foam is irregular, which may be formed by the aggregation of small particles. Therefore, the reduction of loading density will lead to a decrease in large FeCo alloy particles. Figure 3a-3e The SEM image shown also shows that the wrinkles of the graphene foam are very obvious and still have the characteristics of a network of pores.
[0082] In order to further verify that the reticular porous structure of graphene foam and the particles in the composite material are indeed FeCo alloy, this test example also carried out TEM analysis and HRTEM analysis on sample 1#. The results are as follows: Figure 3f and Figure 3g As shown. Figure 3f It can be seen that the FeCo alloy particles are loaded onto the porous network structure of graphene foam and are obviously aggregated in some parts, which is similar to Figure 3aAccording to the calculation of the interplanar spacing and interplanar index, the interplanar spacing of sample 1# is 0.202nm, corresponding to the (110) crystal plane of FeCo alloy. Figure 3g As shown, it can be determined that the particles in the composite material are FeCo alloy particles.
[0083] Test Example 4
[0084] In this test example, XRD analysis was performed on samples 1#-5# respectively, and the obtained XRD spectra are as follows Figure 4 As shown. Figure 4 It can be seen that samples 1-5 all have obvious diffraction peaks at 45°, 65° and 83°, which are respectively determined to be characteristic diffraction peaks of FeCo alloy (110), (200) and (211) crystal planes by comparison with standard cards, confirming the presence of FeCo alloy in the composite material. At the same time, the diffraction peak intensities of the five samples are different, and the FeCo diffraction peak intensity of sample 1# is the highest, which indicates that samples with different component contents are obtained in Example 1 and Comparative Example 1.
[0085] In addition, from Figure 4 It can also be seen that the graphene foam diffraction peak near 25.5° is difficult to observe. This is because in the process of preparing composite materials by hydrothermal method, the graphene foam powder is once again exposed to a high temperature and high pressure reducing environment, and the graphene foam with residual oxygen-containing functional groups is secondary reduced by the strong reducing agent hydrazine hydrate. After the secondary reduction occurs, the lamellar structure of the graphene foam is restacked, and the FeCo alloy particles are embedded between the lamellar layers and the pores in this process. The embedding of magnetic metal particles, namely FeCo alloy particles, will affect the normal arrangement of graphene crystals, reduce the crystallinity of graphene, and reduce the diffraction peak intensity of graphene foam.
[0086] Test Example 5
[0087] In order to further verify the surface chemical composition and valence state of the FeCo alloy / graphene foam composite material, this test example performed X-ray photoelectron spectroscopy analysis on sample 1# with the least graphene foam content. The obtained XPS spectrum is shown in the figure below. Figure 5a-5d As shown. Among them, Figure 5a This is the XPS scanning spectrum of FeCo alloy / graphene foam composite material. Figure 5a It can be seen that the FeCo alloy / graphene foam composite material is composed of four elements: C, O, Fe and Co. Among them, the O element comes from the residual oxygen-containing functional groups in the graphene foam. This result of the XPS total spectrum can directly confirm the existence of graphene foam, which is consistent with the above XRD test results and the analysis and interpretation of the results. Figure 5bThe XPS scanning C1s spectrum of sample 1# shows the characteristic peak of C1s of FeCo alloy / graphene foam composite material. After peak fitting, the peaks with binding energies of 286.55eV, 285.2eV and 284eV correspond to CO, CC and C=C, respectively. It can be seen that there are residual oxygen-containing functional groups on the surface of graphene foam. Figure 5c The XPS scanning Fe2p spectrum of sample 1# shows the characteristic peak of Fe2p of FeCo alloy / graphene foam composite material. Figure 5c The peaks with binding energies of 723.11 eV and 710.31 eV correspond to the 2p 1 / 2 and 2p 3 / 2 Electron spin orbit, compared with the standard XPS spectrum, it can be seen that Fe2p 3 / 2 This corresponds to the Fe-O bond between Fe and the oxygen atoms in the residual oxygen-containing functional groups on the surface of graphene foam. The peak with a binding energy of 729.27 eV in the figure is Fe2p 3 / 2 Satellite companion peaks. Figure 5d The XPS scanning Co2p spectrum of sample 1# shows the characteristic peak of Co2p of FeCo alloy / graphene foam composite material. Figure 5c , Figure 5d The peaks with binding energies of 795.58 eV and 779.84 eV correspond to the 2p 1 / 2 and 2p 3 / 2 Electron spin orbit, similar to Fe, Co2p 3 / 2 The characteristic peaks correspond to the Co-O bonds between Co and the oxygen atoms in the residual oxygen-containing functional groups on the surface of graphene foam. It can be seen that the residual oxygen-containing functional groups on the surface of graphene foam can provide sites for the growth of FeCo alloy to a certain extent, which allows FeCo alloy particles to grow in situ with the residual oxygen-containing functional groups on the surface of graphene foam as the sites.
[0088] Test Example 6
[0089] In order to study the wave absorption performance of FeCo alloy / graphene foam composite materials, according to the transmission line theory, this test example simulates the reflectivity of samples 1#-5# in the frequency range of 2-18 GHz and the thickness of the wave absorption layer of 0-8 mm. The specific steps include: grinding samples 1#-5# respectively and mixing them with paraffin (to disperse and solidify), and then testing the wave absorption performance of the obtained mixture (the specific test method can refer to the 1.2.4 electromagnetic parameter characterization section in "The Effect of Co Doping on the Microstructure and Wave Absorption Performance of RGO / Fe3O4 Composite Materials"). Among them, based on the total weight of paraffin and FeCo alloy / graphene foam composite materials as 100%, the addition amount of samples 1#-5#, i.e., FeCo alloy / graphene foam composite materials, is 60%.
[0090] Among them, the reflectivity RL is generally a negative number. When RL≤-10d B, it can be considered that at least 90% of the electromagnetic waves are absorbed, which is also called effective absorption. At this time, the width of the electromagnetic wave frequency is called the effective absorption bandwidth.
[0091] Among them, the reflection loss three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of sample 1# are shown as follows: Figure 6a-6c As shown; the reflection loss three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of sample 2# are shown as follows Figure 6d-6f As shown; the reflection loss three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of sample 3# are shown as follows Figure 6g-Figure 6i As shown; the reflection loss three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of sample 4# are shown as follows Figure 6j-Figure 6l As shown; the reflection loss three-dimensional model diagram, two-dimensional plane diagram / two-dimensional contour diagram and reflection loss curve of sample 5# are shown as follows Figure 6m-Figure 6o shown.
[0092] from Figure 6a-Figure 6o It can be seen that sample 3# has the best effective absorption loss, and sample 4# has the lowest reflection loss value. Specifically, when the matching thickness of sample 1# is 1.35mm, the minimum (lowest) reflection loss value of -28.64dB is obtained at a frequency of 18GHz; its maximum effective absorption bandwidth is obtained when the matching thickness is 1.6mm, and the effective absorption frequency covers 11.68-18GHz. Compared with samples 3#-5#, the matching thickness corresponding to the lowest reflection loss and maximum effective absorption bandwidth of sample 2# is smaller, 1.72mm and 1.67mm respectively, and its minimum reflection loss and maximum effective absorption bandwidth are -57.20dB and 6.88GHz (11.12-18GHz) respectively. The maximum effective absorption bandwidth of sample 3# performs best among the five samples. When the matching thickness is only 1.85mm, the maximum effective absorption bandwidth can reach 7.2GHz (10.8-18GHz). At the same time, the minimum reflection loss value of sample 3# is also quite impressive. When the matching thickness is 3.17mm, it can achieve -53.89dB at a frequency of 7.12GHz. The minimum reflection loss of sample 4# can reach -61.68dB at a frequency of 3.44GHz when the matching thickness is 5.42mm, which is the best performance among the five samples. When the matching thickness of sample 4# is 1.8mm, the maximum effective absorption bandwidth can reach 6.56GHz (10.28-14.24GHz, 15.2GHz-18GHz).
[0093] from Figure 6m-Figure 6oIt can be seen that the 5# sample does not effectively absorb electromagnetic waves in the frequency range of 2-18GHz. This is because: the graphene foam content in the 5# sample is high, resulting in excessive dielectric properties of the composite material, which leads to poor impedance matching performance, so that a large number of electromagnetic waves cannot enter the interior of the composite material and are directly reflected back from the surface.
[0094] In addition, by comparing the absorbing performance test data of the graphene foam obtained in Example 1 in Test Example 2 with the absorbing performance test data of samples 2# and 4#, it can be seen that from the perspective of minimum reflection loss, samples 2# and 4# have better absorbing performance when used alone as absorbing materials than when graphene foam is used alone as an absorbing material; by comparing the absorbing performance test data of the graphene foam obtained in Example 1 in Test Example 2 with the absorbing performance test data of sample 3#, it can be seen that from the perspective of effective absorbing bandwidth, the effective absorbing bandwidth of sample 3# is larger, indicating that sample 3#, that is, the FeCo alloy / graphene foam composite material, when used alone as an absorbing material, also has better absorbing performance than when graphene foam is used alone as an absorbing material.
[0095] In summary, the embodiment of the present invention successfully prepared five groups of samples by controlling the different addition amounts of graphene foam on the basis of preparing the FeCo alloy / graphene foam composite material by a two-step hydrothermal method. Studies have shown that different graphene foam contents have a great influence on the morphology, structure, saturation magnetization and electromagnetic parameters of the product. With the increase of graphene foam content, the loading area of FeCo alloy continues to increase, and the large particles of FeCo alloy loaded on the graphene sheet continue to decrease. The saturation magnetization and magnetic loss capacity of the composite material continue to decrease with the increase of graphene foam content, while its electrical loss capacity continues to increase. By comparing the wave absorption properties of the five groups of samples, it can be seen that when the content of graphene foam is 2-4% of the mass of FeCo alloy, the FeCo alloy / graphene foam composite materials all show relatively excellent wave absorption properties. Among them, compared with samples 3# to 5#, the matching thickness corresponding to the minimum reflection loss and maximum effective absorption bandwidth of sample 2# is smaller, 1.72mm and 1.67mm respectively, and its minimum reflection loss and maximum effective absorption bandwidth are -57.20dB and 6.88GHz (11.12-18GHz) respectively. The maximum effective absorption bandwidth of sample 3# performs best among the five samples. When the matching thickness is only 1.85mm, the maximum effective absorption bandwidth can reach 7.2GHz (10.8-18GHz). The minimum reflection loss of sample 4# performs best among the five samples, reaching -61.68dB at a frequency of 3.44GHz.
[0096] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A FeCo alloy / graphene foam composite material, characterized in that: The FeCo alloy / graphene foam composite material comprises FeCo alloy particles and graphene foam, wherein the FeCo alloy particles are loaded on the surface of the graphene foam and embedded between the sheets and pores of the graphene foam.
2. The FeCo alloy / graphene foam composite material according to claim 1, characterized in that: Based on the total weight of the FeCo alloy particles as 100%, the content of the graphene foam is 0.5%-4.5%, preferably 1%-4%, and more preferably 2%-4%.
3. The FeCo alloy / graphene foam composite material according to claim 1 or 2, characterized in that: The graphene foam has a three-dimensional porous network structure and a density of 0.012-0.030 g / cm 3 , the maximum value of the real part of the dielectric constant is 6-12.
4. The method for preparing the FeCo alloy / graphene foam composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step 1: adding a divalent iron source, a divalent cobalt source and graphene foam powder into deionized water and mixing them evenly to obtain a metal precursor solution; Step 2: completely dissolving the alkali source in deionized water to obtain an alkali source aqueous solution; Step 3: dropping the alkaline source aqueous solution into the metal precursor solution and mixing evenly, then adding the reducing agent and mixing evenly to obtain a mixed solution; Step 4: subjecting the mixed solution to a hydrothermal reaction. After the hydrothermal reaction is completed, collecting the black precipitate and drying it to obtain the FeCo alloy / graphene foam composite material.
5. The preparation method according to claim 4, characterized in that: In step 1, the divalent iron source includes one or a combination of ferrous chloride, ferrous sulfate, ferrous nitrate and ferrous acetate, and the divalent cobalt source includes one or a combination of cobalt chloride, cobalt sulfate, cobalt nitrate and cobalt acetate.
6. The preparation method according to claim 4 or 5, characterized in that: In step 1, the graphene foam is prepared by a preparation method comprising the following specific steps: Step (1): mixing graphene oxide slurry with a reducing agent, and adding a pore-forming agent to the resulting mixed solution under stirring conditions; Step (2): subjecting the mixed solution obtained in step (1) to a hydrothermal reaction; Step (3): vacuum drying the graphene gel obtained in the reaction in step (2) to obtain the graphene foam; Preferably, step (3) comprises: after the product obtained by the reaction in step (2) is naturally cooled, vacuum drying the obtained graphene gel; Also preferably, the volume ratio of the graphene oxide slurry to the reducing agent is 1:1-1:2, and the volume ratio of the mixed solution formed by the graphene oxide slurry and the reducing agent to the mass ratio of the pore-forming agent is 3:1-6:1; Also preferably, the concentration of the graphene oxide slurry is 1-3 mg / mL; Also preferably, the pore-forming agent includes a pore-forming agent that can sublime under the temperature conditions of hydrothermal reaction and vacuum drying; more preferably, the pore-forming agent includes naphthalene, iodine or camphor balls; Also preferably, the reducing agent comprises ethylene glycol, ethanol, sodium ascorbate aqueous solution or sodium hypophosphite aqueous solution; Also preferably, the temperature of the hydrothermal reaction is 160-240°C and the time is 8-16h; Also preferably, the vacuum drying comprises: first vacuum drying at 60-90° C. for 40-60 h, and then vacuum drying at 110-150° C. for 32-48 h.
7. The preparation method according to claim 4 or 5, characterized in that: In step 2, the alkaline source includes one or a combination of NaOH, urea and ammonia water; Preferably, the molar ratio of the alkali source to the divalent iron ions or divalent cobalt ions is 10:1-20:1, more preferably 15:
1.
8. The preparation method according to claim 4 or 5, characterized in that: In step 3, the reducing agent includes one or a combination of hydrazine hydrate, potassium borohydride and sodium borohydride; Preferably, the molar ratio of the reducing agent to the divalent iron ions or divalent cobalt ions is 60:1-100:1, more preferably 80:
1.
9. The preparation method according to claim 4 or 5, characterized in that: In step 4, the temperature of the hydrothermal reaction is 150-170° C. and the time is 8-12 hours; Preferably, in step 4, the drying is vacuum drying at a temperature of 60-80° C. for 10-16 hours.
10. Use of the FeCo alloy / graphene foam composite material according to any one of claims 1 to 3 as a wave absorbing material.
Citation Information
Cited By
Preparation method of high-performance FeNi alloy graphene foam composite wave-absorbing material
CN120059672A